Improving Collapsibility and Compressibility of Gypseous Sandy Soil Using Bentonite and Kaolinite - Hussein H. Karim; T. Schanz; Maha H. Nasif (Engineering and Technology Journal, 2012)
The sandy soil which covers the surface layer for the investigated area consists of high gypsum content (50%). The soil was found to be a “collapsible” soil. Thus bentonite and kaolinite have been used as an improving agents for such soil. The essential idea of this study represents an investigation of the possibility of using these materials as additives with different percents (5%, 10%, 15%, and 20%) to enhance these soils. A testing program was conducted on 9 models of untreated and treated gypseous soil specimens to study the behavior of such mixes as well as their effects on physical properties, collapsibility and compressibility characteristics. It was concluded that a significant reduction in collapsibility reaching 80 to 82 % for the 10 percent mixed kaolinite and bentonite respectively. Lowest compression index (Cc) and recompression index (Cr) have been obtained using the same percentages of mixed additives. Generally, best improving results have been obtained using bentonite additive (specially the ratio 10%) for its finer grains than those of kaolinite.